2016
DOI: 10.1159/000452970
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Polymorphism of Chromosome Region 9p21 and the Susceptibility of Carotid Plaque

Abstract: Background: Atherosclerosis is a complicated disease governed by genetic, environmental and vascular risk factors, while its relationship with specific genes is still unclear. In recent days, it has been discovered that the single-nucleotide polymorphisms of chromosomal region 9p21 were relevant with the genetic susceptibility of Atherosclerosis. We aimed to figure out the relativity between the gene polymorphism of region 9p21 (rs10757274, rs7044859, rs4977574 and rs496892) and carotid plaque. Methods: With p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We decided to assess the association of atherosclerotic carotid artery stenosis and atherogenic stroke/TIA with four polymorphic variants of the CDKN2B-AS1 and LPA genes. Our selection of genes for the study in a Polish subpopulation was guided by the literature overview and previous studies performed on the atherosclerotic patient populations (1, 1420). We included patients with atherogenic stroke/TIA (a clinical manifestation of atherosclerosis of the arteries) and individuals with a hemodynamically significant stenosis of the artery without brain damage in order to determine if there are differences in the genetic variants in these two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We decided to assess the association of atherosclerotic carotid artery stenosis and atherogenic stroke/TIA with four polymorphic variants of the CDKN2B-AS1 and LPA genes. Our selection of genes for the study in a Polish subpopulation was guided by the literature overview and previous studies performed on the atherosclerotic patient populations (1, 1420). We included patients with atherogenic stroke/TIA (a clinical manifestation of atherosclerosis of the arteries) and individuals with a hemodynamically significant stenosis of the artery without brain damage in order to determine if there are differences in the genetic variants in these two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The basic method to assess the genetic factors for diseases is to evaluate the relationship between a disease entity and polymorphic gene variants, mainly single-nucleotide polymorphisms (SNPs). Previous studies on the link between specific genes and stroke demonstrated inconsistent results (13). Racial/ethnic differences in study subpopulations, differences in the protocol, and small research groups could have all contributed to those discrepancies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation